A behavioral and cognitive neuroscience perspective on impulsivity, suicide, and non-suicidal self-injury: Meta-analysis and recommendations for future research. (December 2017) - Liu, Richard T.; Trout, Zoë M.; Hernandez, Evelyn M.; Cheek, Shayna M.; Gerlus, Nimesha
Highlights: Meta-analysis of behavioral and cognitive impulsivity in relation to self-injury. Behavioral impulsivity was associated with non-suicidal self-injury (NSSI). Behavioral and cognitive impulsivity were associated with suicide attempts. Link with behavioral impulsivity was stronger for past-month than lifetime attempts. Studies with clinically significant NSSI and longitudinal research are needed. Abstract: We conducted a meta-analysis of neurobehavioral and neurocognitive indices of impulsivity in relation to suicidal thoughts and behaviors, as well as non-suicidal self-injury (NSSI). In our systematic review, 34 studies were identified and submitted to a random-effects meta-analysis. A small pooled effect size was observed for the association between behavioral impulsivity and NSSI (OR = 1.34, p <  0.05). A small-to-medium pooled effect size (OR = 2.23, p <  0.001) was found for the association between behavioral impulsivity and suicide attempts, and a medium-to-large pooled effect size was observed for this outcome in relation to cognitive impulsivity (OR = 3.14, p <  0.01). Length of time between suicide attempt and impulsivity assessment moderated the strength of the relation between impulsivity and attempts, with a large pooled effect size (OR = 5.54, p <  0.001) evident when the suicide attempt occurred within a month of behavioral impulsivity assessment. Studies of clinically significant NSSI temporally proximal to impulsivity assessment are needed. Longitudinal research is required to clarify the prognostic value of behavioral and cognitive impulsivity for short-term risk for self-harm.